Efeitos neurocomportamentais promovidos pela cafeína em duas populações de peixe-zebra - Rosa, Luiz Vinícius Costa da (2017)
The zebrafish (Danio rerio) is an emergent model organism in behavioral neuroscience. Several features make zebrafish an attractive vertebrate in scientific researches, such as the small size, low cost, the ease maintenance, abundant offspring, and the fast development until adult phase. The wild-type (WT) and leopard (leo) zebrafish populations present significant behavioral differences, in which leo has a more anxious profile at basal levels. Among the molecules that modulate anxiety-like behaviors, caffeine is the most consumed psicostimulant substance in the western diet. Although the anxiogenic effects of caffeine have been described previously, its influence on populations with different baselines of anxiety levels is unknown. Since behavioral neurophenotyping is easily assessed in zebrafish, especially due to their three dimensional swimming pattern, this study aimed to investigate the effects of caffeine on habituation to novelty stress and its influence on locomotion, exploration, and anxiety-like behaviors. Animals were acutely exposed to caffeine (25, 50, 100, and 200 mg/L) for 15 minutes and further transferred individually to a novel tank. Behavioral analyses and three-dimensional reconstructions of the swimming traces revealed a concentration-dependent effect of caffeine on anxiety-like behaviors by altering vertical activity, freezing episodes, and erratic movements. A prominent anxiogenic effect was verified in WT during habituation to novelty, suggesting an involvement of phenotype in this response. Furthermore, both populations showed abnormal behaviors following 200 mg/L caffeine, reflecting a potential caffeine-mediated neurotoxicity at high concentrations. Altogether, we demonstrate a concentration- and population-dependent effect of caffeine in zebrafish. Besides, the use of different zebrafish populations could serve as a tempting strategy to evaluate anxiety-like behaviors in future pharmacological approaches.